Orientation-selective spin-polarized edge states in monolayer NiI2 - Yu Wang; Xinlei Zhao; Li Yao; Huiru Liu; Peng Cheng; Yiqi Zhang; Baojie Feng; Fengjie Ma; Jin Zhao; Jiatao Sun; Kehui Wu; Lan Chen (Nature Communications)
Abstract Spin-polarized edge states in two-dimensional materials hold promise for spintronics and quantum computing applications. Constructing stable edge states by tailoring two-dimensional semiconductor materials with bulk-boundary correspondence is a feasible approach. Recently layered NiI2 is suggested as a two-dimensional type-II multiferroic semiconductor with intrinsic spiral spin ordering and chirality-induced electric polarization. However, the one-dimensional spin-polarized edge states of multiferroic materials down to monolayer limit has not yet been studied. We report here that monolayer NiI2 was successfully synthesized on Au(111) by molecular beam epitaxy. Spin-polarized scanning tunneling microscopy/spectroscopy experiments visualize orientation-selective spin-polarized edge states in monolayer NiI2 islands. By performing first-principles calculations, we further confirm that spin-polarized edge states are selectively aligning along the Ni-terminated edges rather than the I-terminated edges. Our result will provide the opportunity to tune edge states by selected orientation and to develop spintronic devices in two-dimensional magnetic semiconductors.